Cyberethics morality and law in cyberspace - Spinello, Richard A. (Jones & Bartlett Learning, 2021)
"CyberEthics: Morality and Law in Cyberspace, Third Edition takes an in-depth look at the social costs and moral problems that have arisen by the expanded use of the internet, and offers up-to-date legal and philosophical perspectives. The text focuses heavily on content control and free speech, intellectual property, privacy and security, and has added NEW coverage on Blogging. Case studies featured throughout the text offer real-life scenarios and include coverage of numerous hot topics, including the latest decisions on digital music and movie downloads, the latest legal developments on the Children's Internet Protection Act, and other internet governance and regulation updates. In the process of examining these issues, the text identifies some of the legal disputes that will likely become paradigm cases for more complex situations yet to come."--Provided by publisher.